THE POSSIBLE CONNECTION BETWEEN T TAURI STARS AND UV CETI STARS - HARO, G (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1956)
We have found support for the hypothesis that both the classical flare stars and the flash stars in nebulae belong to the same class of variables, and therefore have a similar origin and represent parallel evolutionary paths. If this hypothesis is accepte
BOL OBS TONAN TACUB
Keywords: POSSIBLE, CONNECTION, TAURI STARS, UV CETI STARS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS